El sentido de la metáfora en los refranes y otros textos líricos orales de Coahuayana - Gloria Vergara (Estudios sobre las Culturas Contemporáneas)
Starting from a concern with break the set idea of metaphor as something distinctive of the great literary woik of art, this article considers the possibility of a convergence between simple and artistic forms by studying the saying and proverbs of Coahuayana. There, in that affinity that Alfono Reyes talks about, is where metaphor gets its first skin, the one which crawls through time and structures, readers and hearers, to come and go in tlie dynamic circle of art´s discursivity. For this reason it becomes necessary to make a brief survey of some of the definitions and cliaracteristics of the sayings and other related texts, so that later we can go more deeply into the consideration of the contrary values tliat allow us to see certain oral texts also as aesthetic forms.